The Institutional Responses of State Islamic Universities to Islamism: Lessons Learned from Three Campuses - Fawaizul Umam; Khoirul Faizin (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2020)
This study attempts to reveal the trend of Islamism and the institutional responses to it in Indonesian higher education, especially in the Perguruan Tinggi Keagamaan Islam Negeri or State Islamic Universities (PTKIN). Three PTKINs, which were UIN Sunan Ampel Surabaya, UIN Maulana Malik Ibrahim Malang, and IAIN Jember, were purposively selected as the research locus. Meanwhile, a case study approach was used to describe Islamism’s trend at these state universities from the 2000s to 2017. It was discovered that the Islamists attempted to infiltrate the campus life through two strategies, which were called persuasive and normative-reeducative. Subsequently, this phenomenon urged the three PTKINs to decide their institutional responses, which have been mainly aimed at deradicalizing campus life and delegitimizing Islamism’s ideology among academics. The institutional responses seem to be pivotal for all PTKINs, especially the three selected schools, because the campus is home to the scientific realm and not a political one. Also, Islamism is a factual threat, both to the integrity of the Unitary State of the Republic of Indonesia (NKRI) and the ideals of the religion as a blessing for the universe.